2018
DOI: 10.1021/acsomega.8b01054
|View full text |Cite
|
Sign up to set email alerts
|

pH-Mediated Collective and Selective Solar Photocatalysis by a Series of Layered Aurivillius Perovskites

Abstract: Semiconductor photocatalysis under natural sunlight is an emergent area in contemporary materials research, which has attracted considerable attention toward the development of catalysts for environmental remediation using solar energy. A series of five-layer Aurivillius-phase perovskites, Bi 5 ATi 4 FeO 18 (A = Ca, Sr, and Pb), are synthesized for the first time. Rietveld refinements of the powder X-ray diffraction data indicated orthorhombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…It is well known that PL spectroscopy studies the efficacy of the photogenerated charge separation and recombination in terms of PL intensity for different nanocomposites. A relatively lower PL intensity indicates the slow or ineffective recombination of electrons and holes, which implies better separation of the photogenerated charges, resulting in an enhancement of the photocatalytic activity . As depicted in Figure d, CT mesocrystals and CTMG nanocomposites show multiple PL emissions centered around 360 nm, when excited at 310 nm.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that PL spectroscopy studies the efficacy of the photogenerated charge separation and recombination in terms of PL intensity for different nanocomposites. A relatively lower PL intensity indicates the slow or ineffective recombination of electrons and holes, which implies better separation of the photogenerated charges, resulting in an enhancement of the photocatalytic activity . As depicted in Figure d, CT mesocrystals and CTMG nanocomposites show multiple PL emissions centered around 360 nm, when excited at 310 nm.…”
Section: Resultsmentioning
confidence: 98%
“…As reported in previous studies that the ∆ values gradually decreases in the order, terminal > preterminal > central octahedral layer for the five-layer Aurivillius phase perovskites in a given series of compounds, is consistent with the second-order Jahn-Teller (SOJT) distortion of d 0 cations in these compounds. [66][67][68] The increase in local octahedral distortion enhances the extent of adsorption of dye molecules on the catalyst surface. Further, the axial distortion parameter, defined as,…”
Section: E (Ev) Vs Nhe E Cb (1) E -mentioning
confidence: 99%
“…As the wastewater is contaminated with multiple dyes rather than a single dye, it is desirable to test the efficiency of a catalyst toward the collective removal of multiple dyes from a mixture. Naresh et al [206] reported that a series of five-layer Bi 5 AFeTi 4 O 18 (A = Ca, Sr, and Pb) compounds not only exhibited collective photocatalytic degradation of RhB-methylene blue and RhB-rhodamine 6G mixture at pH = 2, but also showed almost 100% photo-catalytic selective degradation of methylene blue from the RhB-methylene blue mixture at pH = 11 under natural solar irradiation. In addition, size, morphology, surface area, etc., of a catalyst may greatly affect its catalytic performance.…”
Section: Photo/electro-catalyst Activitymentioning
confidence: 99%